Import variety and productivity in Japan - R.Parsons, Craig (ĐHKT, 2016)
This paper underlines the idea of endogenous growth theory that new or higher quality products have significant impacts on productivity and economic growth. Different with previous studies, this paper uses a quite comprehensive definition of variety, which distinguishes the country of origin of the products.